Kinematics of small-sized skidding system with trajectory in form of arc of circle (Science journal «Technical service of agriculture, forestry and transport systems», 2025)
The study concerns the process of skidding of wood raw materials during felling, formation and rehabilitation of forest stands using mini skidding devices, for example, mini skidders of the leash type. The conditions for skidding of a single round timber in a half-loaded state in flat conditions were selected. The purpose of the study is to mathematically describe the kinematics of the endpoints of the mini skidding system during its movement along a trajectory in the form of an arc of a circle. The theoretical study was carried out by mathematical modeling using the basic principles of theoretical mechanics and the physical characteristics of the subject of work. The skidding method and maneuverability of the skidding device were taken into account. The mathematical model assumes consideration of the main parameters of the forest stand, in particular the layout of trees and their average diameter in the clearing part. The result of the research is the obtained equations and mathematical dependencies, which allow building the trajectory of movement of the end point of the skidding system, provided that the equation of the trajectory of movement of its starting point is known.
Keywords: round timber; mini skidding system; skidding tool; mini skidder; skidding system kinematics